Porcine Deltacoronavirus Nucleocapsid Protein Suppressed IFN-β Production by Interfering Porcine RIG-I dsRNA-Binding and K63-Linked Polyubiquitination - Likai, Ji; Shasha, Li; Wenxian, Zhu; Jingjiao, Ma; Jianhe, Sun; Hengan, Wang; Yaxian, Yan (Frontiers in Immunology, 2019)
Porcine deltacoronavirus (PDCoV) is a newly detected porcine coronavirus causing serious vomiting and diarrhea in piglets, especially newborn piglets. There has been an outbreak of PDCoV in worldwide since 2014, causing significant economic losses in the pig industry. The interferon (IFN)-mediated antiviral response is an important component of virus-host interactions and plays an essential role in inhibiting virus infection. However, the mechanism of PDCoV escaping the porcine immune surveillance is unclear. In the present study, we demonstrated that the PDCoV nucleocapsid (N) protein antagonizes porcine IFN-β production after vesicular stomatitis virus (VSV) infection or poly(I:C) stimulation. PDCoV N protein also suppressed the activation of porcine IFN-β promoter when it was stimulated by porcine RLR signaling molecules. PDCoV N protein targeted porcine retinoic acid-inducible gene I (pRIG-I) and porcine TNF receptor associated factor 3 (pTRAF3) by directly interacting with them. We confirmed that PDCoV N antagonizes IFN-β production by associating with pRIG-I to impede it from binding double-stranded RNA. Furthermore, porcine Riplet (pRiplet) was an important activator for pRIG-I by mediating the K63-linked polyubiquitination. However, PDCoV N protein restrained the pRiplet binding pRIG-I to inhibit pRIG-I K63-linked polyubiquitination. Taken together, our results revealed a novel mechanism by which PDCoV N protein interferes with the early activation of pRIG-I in the host antiviral response. The novel findings provide a new insight into PDCoV on evading the host innate immune response and may provide new therapeutic targets and more efficacious vaccines strategies for PDCoV infections.